The role of gut microbiota in disease management: Ayurvedic perspectives on metabolic diseases and health - Bhawana Jangra; Shreyanshi Kulshreshtha; Alok Goyal; Sanjay M. Jachak (Phytomedicine Plus)
Background: In the past few years, the critical role of gut microbiome in the maintenance of overall health and various diseases has captured significant attention. Various studies underline the importance of maintaining a healthy gut. For centuries, Ayurvedic medicinal plants have been used to treat gut-related diseases and are believed to act as prebiotics, thereby enhancing beneficial gut bacteria. These plants possess incredible therapeutic properties and are able to inhibit TNF-α, NF-κB, COX, LOX, α-amylase, α-glucosidase, etc. They are well documented and used for treating conditions like IBS, chronic diarrhoea, constipation, ulcerative colitis, Agnimandya (digestive impairment), Mandagni (impaired digestive fire) and other gut-related diseases. Purpose: This review is aimed at collecting scientific insights on gut health, focusing on traditional medicinal plants like Babool, Turmeric, Ashwagandha, Ghrit kumari, Tulsi, Harad, Baheda, Amala, and the Triphala formulation. Exploring their phytoconstituents and Ayurvedic formulations, we uncover their role in nurturing gut microbiota and combating various gut disorders. Study design and methods: Consultation of various Databases and search engines such as PubMed, ScienceDirect, ResearchGate, Google Scholar, SciFinder, and other published/unpublished resources provided an overview of the published literature on the topic. Results: The human body is composed of both human cells and microbial cells. These microbes, when present in the gut, are collectively known as gut microbes. These have direct or indirect effects on an individual's health and diseases, viz. dysbiosis, UC, IBD, cardio-vascular diseases, chronic kidney disorders, etc. The interaction of various phytoconstituents present in the MFH plants with the gut microbiota has a two-way effect. While the phytoconstituents can modulate the growth of useful gut bacteria, such as Bifidobacterium and Lactobacillus, these microbes have enzymes that help in the transformation of plant moieties into active metabolites which have beneficial effects. Conclusion: It can be concluded that Ayurvedic MFH plants and formulations can help our gut stay healthy. The available literature describes that these natural remedies are quite effective in treating different gut problems. In conclusion, Ayurvedic remedies could be a great way to keep our digestion in check and improve overall health.